2022
DOI: 10.1029/2022gl100380
|View full text |Cite
|
Sign up to set email alerts
|

How Unexpected Was the 2021 Pacific Northwest Heatwave?

Abstract: The 2021 Pacific Northwest heatwave featured record‐smashing high temperatures, raising questions about whether extremes are changing faster than the mean, and challenging our ability to estimate the probability of the event. Here, we identify and draw on the strong relationship between the climatological higher‐order statistics of temperature (skewness and kurtosis) and the magnitude of extreme events to quantify the likelihood of comparable events using a large climate model ensemble (Community Earth System … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 28 publications
5
35
0
Order By: Relevance
“…A recent study estimated that this heat wave was about two degrees Fahrenheit warmer than it would have been without human influence on the climate (Bercos-Hickey et al 2022), consistent with the increase in mean temperature. An event of this magnitude is likely to occur once in 1000 to 100,000 years (McKinnon andSimpson 2022, Thompson et al 2022). A heat dome would have occurred without climate change, but maximum temperatures would not have been as high (McKinnon and Simpson 2022).…”
Section: Pacific Northwest Heat Wave Of June 2021mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study estimated that this heat wave was about two degrees Fahrenheit warmer than it would have been without human influence on the climate (Bercos-Hickey et al 2022), consistent with the increase in mean temperature. An event of this magnitude is likely to occur once in 1000 to 100,000 years (McKinnon andSimpson 2022, Thompson et al 2022). A heat dome would have occurred without climate change, but maximum temperatures would not have been as high (McKinnon and Simpson 2022).…”
Section: Pacific Northwest Heat Wave Of June 2021mentioning
confidence: 99%
“…An event of this magnitude is likely to occur once in 1000 to 100,000 years (McKinnon andSimpson 2022, Thompson et al 2022). A heat dome would have occurred without climate change, but maximum temperatures would not have been as high (McKinnon and Simpson 2022). estimated that a heat wave of similar magnitude will recur about once in six years by the end of the twenty-first century if concentrations of greenhouse gases do not decrease.…”
Section: Pacific Northwest Heat Wave Of June 2021mentioning
confidence: 99%
“…It is clear that ensemble sizes in the standard CMIP database are not large enough to construct such distributions and provide robust attribution statements. However, recent developments of larger climate model ensemble simulations (up to 40 individual realizations) do provide some insight as to the rarity of such events (McKinnon & Simpson, 2022). Despite these limitations of conventional attribution methods, it is highly likely that anthropogenic climate change influenced the 2021 PNW heatwave.…”
Section: Statistical Modelingmentioning
confidence: 99%
“…Station data for many parts of Europe show an increase in day-to-day temperature variability within the summer season since the 1960s (Krauskopf and Huth, 2022), while increased temperature variability is necessary to account for the magnitude of the 2003 European heat wave (Schär et al, 2004). On the other hand, McKinnon and Simpson (2022) and Thompson et al (2022) found no evidence for faster warming of extremes, relative to the mean for the Pacific North-West.…”
Section: Introductionmentioning
confidence: 96%